Distributive Justice in the Economic Rights of Music Creators and Performers: A Natural Law Analysis of Indonesian Copyright Law - Ashibly Ashibly; Liu Kai; Sherly Nelsa Fitri (Bulletin of Social Studies and Community Development, 2026)
This study examines the problem of distributing economic rights between music creators and performers in Indonesia, a persistent source of legal conflict that existing scholarship has addressed almost exclusively through positive-law doctrinal analysis. The purpose of this study is to critically evaluate the current structure of Indonesian copyright law governing creators' and performers' economic rights through the lens of natural law theory and to identify the normative gaps that produce systemic distributive injustice. Employing normative legal research, this study integrates three analytical approaches: (1) a legislative approach examining Law No. 28 of 2014 on Copyright, Government Regulation No. 56 of 2021, relevant provisions of the Civil Code, and international instruments including the Berne Convention, the Rome Convention, and the TRIPS Agreement; (2) a conceptual approach engaging legal doctrine on intellectual property and collective rights management; and (3) a philosophical approach applying the natural law traditions of the Stoics, Aquinas, Grotius, Locke, Pufendorf, Hutcheson, and Hume as a normative evaluative framework. Legal materials are classified as primary (statutes, regulations, court decisions), secondary (academic literature, journal articles), and tertiary (legal dictionaries). Analysis proceeds deductively, moving from universal natural law principles to their confrontation with positive law norms and current industry practice. The principal finding is that natural law theory treats creators’ economic rights as primary claims grounded in original intellectual labor. In contrast, performers’ rights are secondary and derivative, arising from interpretive contribution. The structural coexistence of direct licensing (Article 9) and blanket licensing (Article 23) without a clear legislative hierarchy produces a distributive gap that violates the natural law principle of suum cuique tribuere. Institutional failures of the Collective Management Institution (CMO) system, characterized by non-transparent reporting and delayed distribution, compound this structural injustice and mirror deficiencies documented in pre-reform European collective management organizations. This study concludes that reform of Indonesian copyright law must establish: a statutory hierarchy privileging direct licensing; minimum royalty standards for commercial use; mandatory real-time reporting and auditing obligations; and a hybrid mechanism combining government-accredited digital licensing platforms with blockchain-based smart contracts for autonomous royalty distribution. Keywords: Copyright; Economic rights of creators and performers; Natural law theory; Distributive justice; Collective management; Indonesian copyright law.